The Impacts of ERP Integration on Information Quality (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2020)
The paper aims at analyzing the relationship between the level of integration of the ERP system and the information quality perceived by managers due to direct and indirect factors. In the latter model, the information quality is affected by the presence of specific features of information flow, defined as the information processing capacity, the frequency of meeting, and the information sharing. To test the research model, a PLS-SEM analysis was applied to a survey conducted in the Italian setting. Empirical results show that the level of integration of the ERP system positively affects the latent variable (features of information flow) and that the features of information flow positively affect the perceived quality of information. Empirical results also suggest that the level of integration of ERP systems can positively and indirectly affect the information quality seen by managers, by the effect of the features of information flow. Managers can benefit from this study for supporting their decision to achieve an optimal level of integration of their ERP systems to enhance the information quality within the firm.